Novel Pathogenic DNAH5 Variants in Primary Ciliary Dyskinesia: Association with Visceral Heterotaxia and Neonatal Cholestasis - Lin, Hong T.; Gupta, Anita; Bove, Kevin E.; Szabo, Sara; Xu, Fang; Krentz, Anthony; Shillington, Amelle L. (Journal of Pediatric Genetics, 2021)
The dynein axonemal heavy chain 5 gene codes for a subunit of axonemal dynein necessary for ciliary motor function. Though research has elucidated the consequences of some variants in this gene, it is still unclear whether many variants in the DNAH5 locus are benign or pathogenic due to the rarity of primary ciliary dyskinesia (PCD, of which Kartagener's syndrome is a subset). Here, we introduce the case of an infant boy presenting with the classical findings of PCD along with visceral heterotaxia and neonatal cholestasis. Genetic testing indicated that the patient is a compound heterozygote with a pathogenic c.8498G > A (known as pathogenic) on the maternally derived allele and two variants of uncertain significance, c.1206T > A and c.7800T > G, on the paternally derived allele. As PCD is autosomal recessive, we conclude that one, or both, of these paternally derived variants are pathogenic. To our knowledge, this is the first time that the clinical implications of c.1206T > A (p.Asn402Lys) and c.7800T > G (p.Ile2600Met) are documented. Furthermore, we use this case as an example to recommend clinicians to assess for PCD and laterality defects when presented with severe infantile cholestasis. While the association of cholestasis with PCD is relatively uncommon, PCD is a risk factor for increased prevalence of biliary atresia and infections, both of which are known causes of cholestasis in early infancy.
Keywords: primary ciliary dyskinesia; Kartagener's syndrome; DNAH5; c.1206T > A; c.7800T > G; cholestasis